How do frogs swallow with their eyes? questions and answers about amphibians - Berger, Melvin; Berger, Gilda; Carr, Karen 1960- (New York Scholastic, 2002)
Presents information about frogs, toads, newts, salamanders, and caecilians in a question-and-answer format
5
Keywords: Amphibians -- Miscellanea -- Juvenile literature; Amphibians -- Miscellanea; Questions and answers